2009
DOI: 10.1007/s00198-009-1129-1
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate reduces osteoclast precursors in osteoporosis

Abstract: We suggest that alendronate mainly acts on mature bone resorbing osteoclasts in the short term, whereas, its long-term administration diminishes their formation by reducing their precursors and serum RANKL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 49 publications
2
29
2
Order By: Relevance
“…As an antiresorptive (antianabolic) agent, it is known to inhibit the enzyme farnesyl pyrophosphate synthase (FPPS), inducing apoptosis in osteoclasts and consequently suppressing osteoclast-mediated bone resorption. (34)(35)(36)(37) Because we observed a significant increase in the percentage and number of LKS cells in the bone marrow and spleen (Fig. 5) and an increase in the activity of osteoclasts in vitro (Figs.…”
Section: Resultsmentioning
confidence: 88%
“…As an antiresorptive (antianabolic) agent, it is known to inhibit the enzyme farnesyl pyrophosphate synthase (FPPS), inducing apoptosis in osteoclasts and consequently suppressing osteoclast-mediated bone resorption. (34)(35)(36)(37) Because we observed a significant increase in the percentage and number of LKS cells in the bone marrow and spleen (Fig. 5) and an increase in the activity of osteoclasts in vitro (Figs.…”
Section: Resultsmentioning
confidence: 88%
“…As we observed that the uptake of ALN by macrophages was reduced as the pH decreased, we could assume that conjugation to BSP could affect the endocytosis of ALN and eventually influence its activity. Interestingly, such findings provide a new clue to explain why ALN has rarely been reported to successfully kill TAM in vivo e though it is well known to do so in vitro [39e41] and has recently excited much interest as potential inhibitors of TAMs [5,42,43]. To date, no study has confirmed that ALN could directly eliminate TAMs in vivo, despite some studies suggesting its effect in stimulating dendritic cells (DCs) [44] or inhibiting angiogenesis and lymph node invasion [45].…”
Section: Discussionmentioning
confidence: 99%
“…These were identified by their expression of CD14/CD11b and were decreased after 12 months of treatment in osteoporotic women (26). In contrast, another study has demonstrated that zoledronate did not reduce the population of osteoclast precursor after 18 months of treatment in osteopenic women, (27) There are also conflicting in vitro data regarding the effect of bisphosphonates on osteoclastogenic cytokines such as IL-1, TNF and circulating levels of RANKL and osteoprotegerin (OPG) (28)(29)(30)(31)).…”
Section: Introductionmentioning
confidence: 99%